Pelatihan Teknik Dasar Menyanyi dan Menjadi Dirigen bagi Siswa Kelas V di SDN 115 Pekanbaru - Laila Fitriah; Andi Idayani; Hengki Satria; Surya Dwi Apsyah (Karawo : Journal of Community Service (KJCS), 2025)
This community service activity aims to improve basic singing skills and the ability to become a conductor for grade V students at SDN 115 Pekanbaru. This training is designed to provide a basic understanding of correct vocal technique as well as choir leadership skills. The methods used include lectures, demonstrations, and hands-on practice, which are expected to increase students' confidence and musical abilities. The results of this activity showed a significant improvement in singing and choir leadership skills, which was measured through pre- and post-training evaluations. In addition, this activity also succeeded in increasing students' interest in musical arts and active participation in school extracurricular activities. Thus, this training is expected to be a model for other schools in developing students' musical artistic potential.